Differential transformation method for solving hybrid fuzzy differential equations - Bahman Ghazanfari; Parvin Ebrahimi (Journal of Hyperstructures)
In this paper, Differential Transformation Method (DTM) was studied for solving Hybrid Fuzzy Differential Equations (HFDEs). The proposed method was also illustrated by some examples and the error comparison was made using Runge-Kutta method of order 4 (RK4).